Integrated traditional Chinese and western medicine nursing of a lung cancer patient with pain after chemotherapy (1例肺癌患者化疗后并发疼痛的中西医结合护理体会) - ZHANG Fengyao (张凤尧); ZHANG Ning (张宁); GAO Chunli (高春利); HAN JianPing (韩建萍); YUE Yuzi (岳玉姿); (孙磊); TANG Ling (唐玲) (中西医结合护理)
This article summarized integrated traditional Chinese and western medicine nursing management for a lung cancer patient with pain after chemotherapy. Routing nursing interventions included routine nursing risk assessment, scientific analgesic strategy and health education. Traditional Chinese Medicine nursing techniques such as Chinese herbal medicine external application, moxibustion, acupoint application and emotion care were carried out to relieve the cancer-related pain after chemotherapy and improve the patient’s quality of life. (本文总结1例肺癌患者化疗后并发疼痛的中西医结合护理经验。护理人员在护理评估、科学止痛、健康教育等常规护理的基础上融入中医特色护理, 运用辨证施护, 开展中药贴敷、艾灸、穴位按摩、情志护理等中医护理适宜技术, 有效改善患者化疗后的癌痛反应, 提高患者生活质量。)